Nigeria : Financial Sector Review, Volume 1. Overview and Macro-Financial Environment - World Bank (Washington, DC, 2013)
This report is a comprehensive review of the Nigerian financial system, covering the following areas: i) macro-financial environment; ii) safety and soundness of the banking system; iii) banking supervision; iv) development finance institutions; v) community banks and commercial banks' rural operations; vi) insurance and pensions; vii) housing finance; viii) money and capital markets; and ix) term finance and leasing. The report is in three volumes: Volume 1 (Overview and Macro-financial Environment) covers the Executive Summary, Overview of the Financial System and Macro-Financial Issues. Volume 2 (Banking Institutions) contains chapters on: i) The Banking System; ii) Assessment of Banking Supervision; iii) Development Finance Institutions; and iv) Community Banks and Commercial banks' rural operations. Volume 3 (Non-Bank Financial Institutions and Markets) includes: i) Insurance and Pensions; ii) Housing Finance; iii) Money and Capital Markets; and iv) Term Finance and Leasing. The Statistical Annex contains relevant data for all the chapters.